Pengaruh Kompensasi Dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada PT Kasih Karunia Sejati Cabang Kabupaten Tangerang - Amri Yahya Hidayat; Aden Prawiro Sudarso (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine the effect of compensation and motivation on employee work productivity at PT. Kasih Karunia Sejati Cabang Tangerang Regency. The research method used used descriptive quantitative methods. The sample used was a saturated sample using the entire population of 60 PT. Kasih Karunia Sejati Cabang Tangerang Regency. Data analysis techniques include validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. From the results of this research it can be concluded that compensation has a positive and significant influence on employee work productivity with a value of T_count > T_table or (12.779 > 1.672) and is strengthened by a significance value of 0.000 < 0.05. Thus, Ho_1 is rejected and H_1 is accepted. Motivation has a positive and significant influence on employee work productivity with a value of T_count > T_table or (12.364 > 1.672) and is strengthened by a significance value of 0.000 < 0.05. Thus, Ho_2 is rejected and H_2 is accepted. Compensation and motivation have a positive and significant influence on employee work productivity with a value of F_count > F_table or (176.730 > 3.159) and is strengthened by a significance value of 0.000 < 0.05. Thus, Ho_3 is rejected and H_3 is accepted. Compensation and motivation on employee work productivity have a regression effect of Y = 4.298 + 0.500X1 + 0.403X2 + α. The result of the R-square value (coefficient of determination) is 0.861, it can be concluded that the variables compensation (X1) and motivation (X2) together have an influence contribution to the variable (Y) of 86.1% while the remaining 13.9% is influenced by other factors or other variables not studied.